Bhopal Gas Tragedy 1984: chemical catastrophe - Abu Kassim, Nur Sofiah; Ismail, Muhammad Farhan; Khairul, Nurzahira Batrisya; Mahmood, Wan Auni Masturina; Hanafi, Noor Hanny Nazirah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
On the night of December 2–3, 1984, a catastrophic gas leak at the Union Carbide pesticide plant in Bhopal, India, released tons of toxic methyl isocyanate (MIC) into the air. Within hours, thousands of people died, and over half a million were exposed to the poison and many suffering long-term health effects, disabilities, or loss of livelihood. The Bhopal disaster remains the world’s worst industrial chemical accident. This e-book presents the true story of The Bhopal Tragedy, examining the incident through the lens of Chemical Safety Management. It highlights how poor hazard identification, lack of risk control measures, insufficient emergency preparedness, and weak regulatory oversight contributed to the scale of the disaster. Key safety failures, such as disabled safety systems, inadequate staff training, and the absence of proper chemical storage protocols, are analyzed to emphasize the critical importance of proactive chemical safety practices. This case study reinforces the core learning outcomes of Chemical Health and Safety Management courses, encouraging readers to apply best practices and lessons learned from Bhopal to prevent future industrial disasters.